Development and Comparison of New High‐Efficiency Dry Powder Inhalers for Carrier‐Free Formulations. Issue 2 (4th December 2013) - Behara, Srinivas R. B.; Longest, P. Worth; Farkas, Dale R.; Hindle, Michael
<x xml:space="preserve">Abstract</x> High‐efficiency dry powder inhalers (DPIs) were developed and tested for use with carrier‐free formulations across a range of different inhalation flow rates. Performance of a previously reported DPI was compared with two new designs in terms of emitted dose (ED) and aerosolization characteristics using in vitro experiments. The two new designs oriented the capsule chamber (CC) at different angles to the main flow passage, which contained a three‐dimensional (3D) rod array for aerosol deaggregation. Computational fluid dynamics simulations of a previously developed deaggregation parameter, the nondimensional specific dissipation (NDSD), were used to explain device performance. Orienting the CC at 90° to the mouthpiece, the CC90‐3D inhaler provided the best performance with an ED = 73.4%, fine particle fractions (FPFs) less than 5 and 1 μm of 95.1% and 31.4%, respectively, and a mass median aerodynamic diameter (MMAD) = 1.5 μm. For the carrier‐free formulation, deaggregation was primarily influenced by capsule aperture position and the NDSD parameter. The new CC‐3D inhalers reduced the percent difference in FPF and MMAD between low and high flows by 1–2 orders of magnitude compared with current commercial devices. In conclusion, the new CC‐3D inhalers produced extremely high‐quality aerosols with little sensitivity to flow rate and are expected to deliver approximately 95% of the ED to the lungs. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:465–477, 2014